Comparison of the health of Roma and non-Roma children living in the district of Teplice - Dostal, Miroslav; Topinka, Jan; Sram, Radim J (International journal of public health, 2010)
OBJECTIVES: To compare the morbidity of 66 Roma and 466 non-Roma children born and living in a diffused type of habitation in the district of Teplice. METHODS: For each child, a complete list of illnesses that pediatricians recorded using ICD-10 codes for all physician visits and/or hospitalizations was obtained. RESULTS: At the age 0-2 years the Roma/non-Roma rate ratios (RR) of the incidence of influenza (RR 1.6), otitis media (RR 2.3), intestinal infectious diseases (RR 1.7) and viral illnesses (RR 6.3) were statistically associated with ethnicity. The higher incidence of bronchitis (RR 1.7) and pneumonia (RR 2.2) in the Roma children was associated with the low education of mothers and not with ethnicity. CONCLUSIONS: At the age of 0-2 years the incidence of influenza, otitis media, intestinal infectious diseases and of viral diseases was significantly higher in Roma than in non-Roma children and was not associated with education of mothers. There was no increase in the morbidity of Roma children over the non-Roma children at the age of 2-6 years. The prevalence of allergies in Roma children was extremely low.
Keywords: novorozenec; Infant, Newborn; Infant; Humans; kojenec; dítě; Child; následné studie; Female; Romové; infekční nemoci; lidé; Roma; Health Status Disparities; předškolní dítě; ženské pohlaví; Male; incidence; Incidence; Czech Republic; Communicable Diseases; disparity zdravotního stavu; Česká republika; mužské pohlaví; Child, Preschool; Follow-Up Studies